The Studentification of Low-Wage Service Work in Sweden: Who Participates? - Kallos, Anna (Nordic Journal of Working Life Studies, 2024)
The study examines trends in part-time employment among school students (15–20 years old) in Sweden. Using data from the Swedish Labor Force Survey (2006–2019) and population-based registries, the article analyzes developments in employment rates and work patterns. The results indicate a rapid increase in part-time work, particularly in the hospitality sector, which underscores how young student-workers have become an important source of non-standard, low-wage labor. Using zero-inflated negative binomial regression modeling, the study shows that female students and those with better grades are more likely to have jobs during school. However, students with lower parental income and education are predicted to work longer hours. Since intensive part-time work during school is associated with risks such as poor academic success and school dropout, the findings raise concerns that the patterns of part-time work among young students may perpetuate class-based inequalities.